Experimental study on the performance of a novel in–house heat pump water heater with freezing latent heat evaporator and assisted by domestic drain water. (1st February 2019) - Guo, Xiaochao; Ma, Zhixian; Ma, Liangdong; Zhang, Jili
Highlights: A novel heat pump water heater with a freezing latent heat evaporator was proposed. The energy recovery of the novel system was 4.4 times that of the conventional one. The novel system could save 60% of energy compared with the electrical water heater. The heat transfer coefficient increased significantly at the moment of freezing. Abstract: The temperature of domestic drain water is relatively high, but its flux is sometimes insufficient as a heating source. Thus, the conventional wastewater source heat pump water heater is incapable of meeting user heating demand given the limited sensible heat temperature difference in many situations. To address this problem, a novel in–house heat pump water heater with a freezing latent heat evaporator and assisted by domestic drain water was proposed. A prototype of the system was first constructed to determine the performance of the system. An experiment was then conducted, in which a parallel helical coil tube evaporator was designed and developed to extract freezing latent heat from domestic drain water. Experimental data was obtained in different experimental conditions. Results of the investigation show that the heat pump water heater with a freezing latent evaporator recovers 3.4 times more energy than the conventional wastewater source heat pump water heater, and saves 60% energy compared with the traditional electric water heater. Furthermore, an interesting result is that the heat transfer coefficient increased significantly at the moment the wastewater was just frozen. This paper provides a reference for the wastewater source heat pump water heater to extract freezing latent heat from domestic drain water.